2015
DOI: 10.1093/ofid/ofv208
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practices of Healthcare Personnel Regarding the Transmission of Pathogens via Fomites at a Tertiary Care Hospital in Karachi, Pakistan

Abstract: Background. Fomites are objects that can become colonized and serve as vectors in the transmission of pathogenic microorganisms. Literature examining the knowledge of healthcare personnel about this method of spread of infection is lacking. We conducted a study to assess the knowledge, attitude, and practices of healthcare personnel across different areas of patient care regarding the spread of infections at a tertiary care hospital in Karachi, Pakistan.Methods. A descriptive, cross-sectional study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
2
12
1
Order By: Relevance
“…We found fairly satisfactory level of knowledge of hospital staff on one hand and the dismal scenario of practices revealed on the other hand. Similar to our results in a study from Karachi (Pakistan), ‘vast gap’ was found between the knowledge and practices of health-care personnel [ 34 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found fairly satisfactory level of knowledge of hospital staff on one hand and the dismal scenario of practices revealed on the other hand. Similar to our results in a study from Karachi (Pakistan), ‘vast gap’ was found between the knowledge and practices of health-care personnel [ 34 ].…”
Section: Discussionsupporting
confidence: 90%
“…Several earlier studies conducted in the resource-limited institutions mostly belonging to the LMICs have reported practices similar to our findings [ 34 , 35 , 36 , 37 , 38 ], which are in sharp contrast to a study from a resource-rich institution in north India [ 27 ].…”
Section: Discussionsupporting
confidence: 76%
“…Similar microorganisms were encountered by health professionals in other studies. 2,13,14 The mode of transmission of Nosocomial Infections cited by medical professionals was direct contact with patients and staff, aerosols from patients, unsterile instruments and fomites. All doctors were aware of universal safety precautions and believed that Nosocomial Infections are a major concern to them in their respective practice and also agreed for its inclusion in Medical education syllabus.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the stethoscope, which is universally used as a medical device by healthcare workers, is more likely to be contaminated by microorganisms, if it is not disinfected and may transmit pathogens from one patient to another [1419]. For this reason, regular cleaning with a suitable disinfectant is decisive and part of a multi-barrier strategy to prevent HCAIs; since failure to properly disinfect or sterilize equipment carries not the only risk associated with breach of host barriers but also risk for person-to-person transmission and transmission of environmental pathogens (e.g., Pseudomonas aeruginosa ) [14, 20].…”
Section: Introductionmentioning
confidence: 99%